2021
DOI: 10.1108/medar-07-2020-0965
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for sustainable finance: does fair value measurement fit for long-term equity investments?

Abstract: Purpose The purpose of this paper is to discuss whether fair value accounting fits for long-term equity investments, which are considered key to retool economies according to sustainability criteria. In doing so, the paper focuses on the European Union and addresses the European Commission’s (2018a) concern that current accounting rules are unfit for achieving the United Nations Sustainable Development goals and the targets of the Paris Agreement on climate change. Design/methodology/approach The paper groun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…In total, 20 South African accountants, experienced in implementing fair value accounting requirements, were interviewed. The findings complement existing studies on fair value that deal mainly with developed economies, are quantitative or involve fair value's history, ideology, assumptions and appropriateness (Barlev and Haddad, 2003; Penman, 2007; Whittington, 2008; Power, 2010; Georgiou and Jack, 2011; Palea and Maino, 2013; Brousseau et al , 2014; Durocher and Gendron, 2014; Zhang and Andrew, 2014; Barker and Schulte, 2017; Chen et al , 2017; Haswell and Evans, 2018; Palea, 2019).…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…In total, 20 South African accountants, experienced in implementing fair value accounting requirements, were interviewed. The findings complement existing studies on fair value that deal mainly with developed economies, are quantitative or involve fair value's history, ideology, assumptions and appropriateness (Barlev and Haddad, 2003; Penman, 2007; Whittington, 2008; Power, 2010; Georgiou and Jack, 2011; Palea and Maino, 2013; Brousseau et al , 2014; Durocher and Gendron, 2014; Zhang and Andrew, 2014; Barker and Schulte, 2017; Chen et al , 2017; Haswell and Evans, 2018; Palea, 2019).…”
Section: Discussionsupporting
confidence: 72%
“…Initially, respondents indicated that disclosures are fundamental for users' understanding of how businesses create value for investors (R2, R3, R5, R6, R7, R10, R13, R17 and R19). Respondent 10 went so far as to argue that the disclosure of fair value was more useful than recognising changes in the values as part of the accounting system, sentiments echoed by Palea (2019). These views were, however, contradicted.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations